Utility of fecal calprotectin as a discriminative biomarker between ulcerative colitis and irritable bowel syndrome and its ability to be used for the assessment of the remission stage of ulcerative colitis - Hossam M Elsaadany; Mohammed F Almaghraby; Awatif A Edrees; Yasser M Elsherbiny; Roobina K Kumar (SpringerOpen, 2016)
Background and aim Fecal calprotectin (FC) has been proposed in recent studies as a sensitive, specific biomarker for the diagnosis of ulcerative colitis (UC). Hence, the present study sought to investigate the efficacy of FC for the diagnosis and monitoring of UC, as well as to assess the correlation of FC with other disease activity indexes. Research design and methods The present study included 96 consecutive patients who presented with lower gastrointestinal complaints. Patients were classified into two groups: group I (which included patients with UC) and group II (which included patients with irritable bowel syndrome); then, according to the disease activity, group I was subdivided into the following: group Ia (which included patients with active UC) and group Ib (which included only those patients of group Ia who were in the remission stage of UC). For all patients, erythrocyte sedimentation rate and C-reactive protein were determined; moreover, all patients underwent quantitative determination of calprotectin in stool samples, abdominal ultrasonography, and complete colonoscopy with biopsies for the histopathological examination to assess the disease severity by using the UC activity index according to the Mayo endoscopic and Geboes histological scores. The diagnostic validity of FC levels in correlation with Mayo Disease Activity Index (MDAI) was then investigated. Results FC levels showed highly significant increase in patients with active UC compared with inactive UC and irritable bowel syndrome (524.17 ± 48.0 vs. 184.48 ± 3.33 and 47.17 ± 5.32 mg/kg, respectively, P < 0.001). FC level has 100% accuracy, sensitivity, specificity, positive predictive value, and negative predictive value in distinguishing UC patients from the control group at a cutoff value of 140 mg/kg, but at a cutoff value of 223 mg/kg FC level shows 93.4% accuracy, 89.8% sensitivity, 97% specificity, 97.4% positive predictive value, and 55% negative predictive value to distinguish the active phase from the remission phase of UC. In addition, there was a statistically significant proportional correlation between FC and the MDAI, but the correlation between FC and histological inflammatory activity statistically was more significant than with MDAI (r = 0.75, P < 0.001). Conclusion FC level is an accurate, noninvasive biomarker in clinical practice with high specificity and sensitivity for the diagnosis and monitoring of UC, as well as good marker for the evaluation of disease activity. Therefore, it can be used as a monitoring test to assess medical response and to predict clinical relapse of the disease.